Pre-School Teacher Professionalisation in the Workplace: The Perspective of the Beginning Teacher with Teaching Assistant Experience - Anužienė, Birutė; Šatienė, Salomėja (Journal of Education Culture and Society, 2026)
Aim. The aim of this study is to investigate the professionalisation of beginning pre-school teachers in the workplace, focusing on the analysis of their experience gained working as teaching assistants and their life stories. Methods. The research is based on a phenomenological research strategy and adopts a biographical research approach by examining and evaluating the life stories presented as participants’ personal experiences and views. The sample consists of homogeneous cases - beginning pre-school teachers with teaching assistant experience (n=8) from different Lithuanian pre-school institutions. Results. The research findings reveal four main meanings of teachers’ life stories: (a) reconstruction of the professional identity of beginning pre-school teachers striving for professionality in the transition from the teaching assistant to the teacher position; (b) workplace learning behaviour of beginning pre-school teachers in terms of cognitive, emotional, motivational and social dimensions; (c) identification and integration of practical knowledge and skills acquired as a teaching assistant; (d) transformation of teaching practice as a result of learning in the workplace. Conclusions. The insights obtained in this study contribute to better understanding of the peculiarities of the pathway of professionalisation in the workplace through transformation of the teaching practice in transition from the teaching assistant to the teacher position. The research-training approach adopted in the present study proves to be a useful tool in teacher continuous learning, which allows the teachers participating in research to engage in individual and collective reflection making the meaning of their experience.